Implementasi Kebijakan Pengelolaan Dana Desa Pada Kecamatan Kei Besar Besar Kabupaten Maluku Tenggara - Belnard, Henderika; Rengifurwarin, Zainal Abidin; Ohoiwutun, Stanislaus K.; Rejaan, Silvius; Renwarin, Martinus (Jurnal Ilmiah Global Education, 2024)
There needs to be implementation of village fund management to be able to measure the success of the use of funds in the district of Maluku Tenggara. Weak accountability and human resources in support of the implementation of these funds and still weak communication between the village government and the Maluku South East district government. In addition, the weakness of the control functions of the Village Visit Authority (BPD) so that the village government manages without a transparent supervisory function. The research method used is qualitative descriptive by conducting in-depth interviews with selected information. As for the findings of the research, (1) the formal and informal media of the village are able to support the implementation of the policy of the Village Fund. (2) the geographical factors affecting the planning of village development. (3). Resources are very supportive of the village fund planning managers.